(untitled) (Journal of Humanitarian and Applied Sciences, 2025)
Wadi Tergat is one of the significant valleys in western Libya, representing an integrated environmental and geographical system shaped by the interaction of natural and human factors. This study aims to analyze the morphometric and hydrological characteristics of the valley and to assess their impact on local agricultural and economic activities. The research employs spatial analysis methods using Geographic Information Systems (GIS) and remote sensing to identify slope patterns, soil distribution, and surface runoff zones. The findings indicate that Wadi Tergat exhibits notable geomorphological diversity that directly influences land use patterns, while seasonal floods serve as an important water resource that can be utilized to promote sustainable agriculture. The study recommends developing a comprehensive strategy for managing the valley’s resources to achieve a balance between economic development and the preservation of the natural environment.